Negotiating the Paradox of Virtual Embodiment in the Classroom: Virtual Ethnicity, the Seductions of Potential, and the Assumption of Access - Burlein, Ann (Journal of religion and popular culture, 2003)
This paper explores how the practice of critical thinking in religious studies is being re-shaped by the Internet. My jumping off point is pedagogy: information technologies seem to embody world religions for my students at the same time as their use makes it more difficult for students to engage with issues of justice. Arguing that different media facilitate different scenes of interpellation, I contend that the web's style of immersion through interactivity solicits a different kind of citizen: one who assumes access to racialized/ethnicized others as both a consumer right and as proof of technological liberation.